Helicobacter pylori virulence genes in patients with gastroduodenal diseases - Thapa, Jiwan; Shrestha, Ramila; Thapa, Suresh; Baral, Shankar; Yadav, Bhuwneshwer; Thapa, Anuja Bhandari (Journal of Advances in Internal Medicine, 2025)
BACKGROUND Helicobacter pylori cause various gastroduodenal diseases. Infection is acquired mostly from feco-oral route, resides in gastric epithelium by forming a protective environment that evades host immune damage. Virulence factors and host response determine the severity of disease and duration of infection. The objective of this study was to identify cytotoxin associated gene A, vacuolating cytotoxin gene A and urease gene C by polymerase chain reaction in helicobacter pylori positive gastric lesions obtained during endoscopy in symptomatic patients. METHODS This is a cross sectional, hospital based observational study carried out at gastroenterology department, Bir hospital during November 2019 to January 2021. Giemsa stain was done to identify helicobacter pylori in gastric biopsies. Cytotoxin associated gene A, vacuolating cytotoxin gene A and urease C gene were identified by polymerase chain reaction among the positive lesions. Data was entered in Microsoft Excel 19 and descriptive analysis was done. RESULTS Gastritis (n=114, 67.8%) was the commonest lesion identified. Helicobacter pylori was positive among 65 gastric biopsies (38.6%) by Giemsa stain. Higher frequency of cytotoxin associated gene A (n=63, 96.9%) compared to vacuolating cytotoxin gene A (n=50, 76.9%) was detected in these positive lesions. Urease C gene was detected in these 63 patients (37.5%) by polymerase chain reaction. CONCLUSIONS Cytotoxin associated gene A was the commonest virulence gene in gastroduodenal diseases. Polymerase chain reaction had a good diagnostic role for identification of helicobacter pylori.